The Linguistic Features Uniqueness of the Students’ Written Discourse in Online Learning - Farida Hasan; Maemuna Muhayyang (Universitas Negeri Makassar, 2018)
This research aimed at finding and describing the types and the uniqueness of linguistic features used by the students in their written discourse in BritishEnglishClass.com. The researcher applied a descriptive qualitative method. The data collection was done using document analysis in form of chat history in Whatsapp and taking ten students as the participants of this study. The result of the analysis showed that the students used six types of linguistic features namely (1) Lexical features in terms of the use of interjection, abbreviation, word letter replacement, word combination, code switching, code mixing and diction, (2) Orthographic features in terms of word spelling and capitalization, (3) Grammatical features in terms of ellipsis, passive voice, verb use, and personal pronoun, (4) Discourse features in terms of the use of interactional features and the stream of consciousness, (5) Paralinguistic and Graphic in terms of emoticon usage and excessive punctuation and, (6) other features in terms of written out laughter . These features are unique because they are different from the standard form of the language. It can be seen also from the use of abbreviation and ellipsis that shorten the students’ sentence, the use of emoticon representing the emotions and psychical activity, the use of lower and upper case to represent the sound and the intonation of the student’ sentence, the abandonment of convention of capitalization of proper nouns and the first words of sentences, and the creative orthography of some words. The linguistic features used by the students were different from the standard form and their function that allowed the student to express and emphasize their intention, meaning and emotion in the chat room make the students’ written discourse in online learning is uniqueKeywords: uniqueness, linguistic features